Cloning and characterization of the UePrf1 gene in Ustilago esculenta. Issue 12 (30th March 2018) - Zhang, Yafen; Liu, Honglei; Cao, Qianchao; Ge, Qianwen; Cui, Haifeng; Yu, Xiaoping; Ye, Zihong
Abstract: Ustilago esculenta, an obligate parasite of Zizania latifolia, is a typical dimorphic fungus which induces host stem swelling and inhibits host inflorescence development, but is not found in host leaves. Previous studies have shown that dimorphic switching is essential for fungal pathogenicity and is regulated by protein kinase A and mitogen-activated protein kinase (MAPK) signaling pathways that are integrated by Prf1 in Ustilago maydis . In this study we identified a Prf1 homolog in U. esculenta, designated UePrf1, encoding 830 amino acids with a conserved high mobility group domain located between amino acids 124 and 195. UePrf1 was upregulated during the mating process, which induces dimorphism in U. esculenta . In vitro, UePrf1 mutants showed defects in the mating process, including cell fusion and hyphal growth. UePrf1 mutants also show reduced expression of a genes, even during the cell fusion process. Additionally, the defect in hyphal growth of the UeKpp2 and UeKpp6 mutants (MAPK signaling pathway mutants) was partially counteracted by UePrf1 overexpression, along with induced b gene expression. These results provide evidence that UePrf1 is a key factor coordinating dimorphism in U. esculenta and suggest a conserved role for UePrf1 in the regulation of the a and b genes. Abstract : UePrf1 is cloned and characterized to be necessary for cell fusion and hyphal growth in vitro by influencing the expression of a and b mating-type genes.